Systematic Literature Review of Disruption Era in Indonesia: The Resistance of Industrial Revolution 4.0 - Fadilurrahman, M.; Ramadhani, Ramadhani; Kurniawan, Tahta; Misnasanti, Misnasanti; Shaddiq, Syahrial (Journal of Robotics and Control (JRC), 2021)
The plethora of research in the multidisciplinary fields has been proved the disruption era. However, it might be several boundaries in the global context. Thus, this research attempts to identify dominant fields which consist of implementing the law, governance, management trajectory, and system of higher education in Indonesia. Furthermore, the qualitative method of the systematic literature review is used to examine the implication, and therefore this study produces four findings.Â  Firstly, the most prominent enabling contexts are to ensure the implementation of the law and the conceptualisation of policies. Secondly, adopting effective and efficient bureaucracy bases on electronic governance (e-governance). Thirdly, management trajectory has been aimed to fill the gaps in this context. Finally, this study also intends to unveil preliminary actions toward the higher education system by networking infrastructures. The outcomes might be considered as pathways for accelerating the progress related to authorities, companies, and institutions. By way of conclusion, in order to attain better provision, measuring the process of the Indonesia disruption realm is a critical phase to elucidate the current circumstance, elaborate the gaps, and foresee the priority actions concerning the disruption era in Indonesia.